2019
DOI: 10.3390/app9071284
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Control of a Non-Linear System Using a Modified Sliding Mode Control

Abstract: Trajectory tracking is an essential requirement in robot manipulator movement and localization applications. It is a current research topic of interest, and several researchers have proposed different schemes to achieve the task accurately. This research proposes efficient control of a hydraulic non-linear robot manipulator using a modified sliding mode control, named proportional derivative sliding mode control with sliding perturbation observer (PDSMCSPO), to overcome parameter uncertainties and non-linearit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…SMC is robust and has good performance against perturbation. There are many practical applications of SMC includes; motor driver, robot position control, and underwater vehicles [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In SMC the main idea is to design the sliding surface and move the system states to the designed sliding surface [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…SMC is robust and has good performance against perturbation. There are many practical applications of SMC includes; motor driver, robot position control, and underwater vehicles [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In SMC the main idea is to design the sliding surface and move the system states to the designed sliding surface [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al studied the modification of the integral sliding variable degrades, and suggested that the switching element is smoothed by using a low-pass filter [21]. More works related to sliding mode control can be found in [22,23]. In [22] a SMC was designed to control a washout filter with constant impedance and nonlinear constant power loads.…”
Section: Introductionmentioning
confidence: 99%
“…More works related to sliding mode control can be found in [22,23]. In [22] a SMC was designed to control a washout filter with constant impedance and nonlinear constant power loads. In [23] a PDSMC was designed to collaborate with a sliding perturbation observer to control a robot manipulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage after the shutdown of an NPP is dismantling, and recently, this phase has become a critical problem. After the NPP disaster in Fukushima, Japan, NPP dismantling has gained worldwide attention [5]. As a result, researchers and various industries have continued to introduce new robot technologies that are feasible for NPP dismantling in which robots are mainly used for cutting and cleaning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%